Uniting Native Capillary Electrophoresis and Multistage Ultraviolet Photodissociation Mass Spectrometry for Online Separation and Characterization of Escherichia coli Ribosomal Proteins and Protein Complexes - Mehaffey, M. Rachel (Anal Chem, 2020)
With an overarching goal of characterizing the structure of every protein within a cell, identifying its interacting partners, and quantifying the dynamics of the states in which it exists, key developments are still necessary to achieve comprehensive native proteomics by mass spectrometry (MS). In practice, much work remains to optimize reliable online separation methods that are compatible with native MS and improve tandem MS (MS/MS) approaches with respect to when and how energy is deposited into proteins of interest. Herein, we utilize native capillary zone electrophoresis coupled with MS to characterize the proteoforms in the Escherichia coli 70S ribosome. The capabilities of 193 nm ultraviolet photodissociation (UVPD) to yield informative backbone sequence ions are compared to those of higher-energy collisional dissociation (HCD). To further improve sequence coverage values, a multistage MS/MS approach is implemented involving front-end collisional activation to disassemble protein complexes into constituent subunits that are subsequently individually isolated and activated by HCD or UVPD. In total, 48 of the 55 known E. coli ribosomal proteins are identified as 84 unique proteoforms, including 22 protein-metal complexes and 10 protein-protein complexes. Additionally, mapping metal-bound holo fragment ions resulting from UVPD of protein-metal complexes offers insight into the metal-binding sites.